Exceptional Sluicing Cases in Japanese - Oguro, Takeshi (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2014)
It has been standardly assumed since the seminal work of Ross (1969) and the extensive study by Merchant (2001) that English sluicing is a result of WH-movement to COMP followed by TP-deletion. Thus the second conjunct of (1a) is considered to be like (1b). (1) a. Somebody just left -- guess who. b. Guess [CP who [TP t just left]]. Japanese sluicing, on the other hand, is assumed to involve a cleft structure by many authors, including Nishiyama, Whitman, and Yi (1996) and Kuwabara (1997). Their chief motivation comes from the optional presence of a copula. (2) Mary-ga nanika-o katta rasii ga, boku-wa Mary-NOM something-ACC bought likely but I-TOP [nani-o (da) ka] wakaranai. what-ACC COP Q not-know It is likely that Mary bought something, but I don't know what. In (2), the question marker ka can be preceded by the copula da, which makes it difficult to maintain a WH-movement analysis (Takahashi 1994). The cleft approach seems superior in this respect and it conforms to the fact that Japanese is a non-WH-movement language. In this study, I show that there are cases in Japanese where the cleft analysis fails and the English type of analysis is applicable.